Research Theatre, Climate Change, and the Ecocide Project: A Casebook - Chaudhuri, U. author. aut Link
XII, 128 p. 16 illus.
Keywords: Theatre is a uniquely powerful site for the kind of thinking called for by the crises of climate change. Encompassing academic research, theatre work-shopping, playwriting, dramaturgy, and theoretical writing, this book offers a practical, theoretical, and critical engagement with the urgent issue of making art in the age of climate change.